The Effect of Electronic Tindak Lanjut Tensiku (e-Titenku) Model to Knowledge of Coronary Heart Disease Prevention - Sidik Awaludin; Galih Noor Alivian; Aprilia Kartikasari; Dwi Novitasari (Journal Of Nursing Practice, 2023)
Background: Cardiovascular disease is still a major global health problem. Hypertension is the most risk factor for the incidence of cardiovascular disease and increases the risk of death. Primary and secondary prevention efforts are needed by increasing patient awareness of identifying risk factors and carrying out preventive management. “Electronic-Tindak lanjut Tensiku”, known as e-TITENKU, is a web and smartphone-based application designed to manage coronary heart disease prevention in patients with hypertension. Purpose: The purpose of this study was to determine the effect of the e-TITENKU intervention model on knowledge of coronary heart disease prevention. Methods: This research design is true experiment pre and post control group design. The sample size is 120 respondents with primary hypertension in Banyumas Regency, Indonesia. The sampling technique used is simple random sampling. The inclusion criteria included respondents with primary hypertension, adults aged 40-65 years, cooperative and willing to be respondents, while the exclusion criteria were respondents experienced complications of other diseases due to hypertension. Results: The results of the study were that the mean score of pre-intervention knowledge in the treatment group was 3.65, while in the control group was 3.43. While the mean score of knowledge after the intervention was 7.98 and the score of knowledge on the second measurement in the control group was 3.53. Conclusion: The e-TITENKU intervention model was able to increase the knowledge score of coronary heart disease prevention. This model can be used by nurses in hospital and community services.